161k views
0 votes
Simplify 7^6 ⋅ 7^5. 49^11 49^35 7^11 7^35

2 Answers

2 votes

Answer: 7^11

Step-by-step explanation:

The rule is

a^b*a^c = a^(b+c)

Note how each base is the same (both 'a' each time). The rule wouldnt work if the bases were different.

So,

a^b*a^c = a^(b+c)

7^6 * 7^5 = 7^(6+5)

7^6 * 7^5 = 7^11

In short, you just add the exponents.

Keep in mind that the base stays at 7 the whole time. It might be tempting to do 7*7 = 49, but that would be incorrect.

User XCander
by
5.0k points
5 votes

Answer:

=8.310133e+125

Step-by-step explanation:

Given that:

= 7^6 ⋅ 7^5. 49^11 49^35 7^11 7^35

By making all bases same (equal to 7)

= 7^6 ⋅ 7^5. 7^2*11. 7^2*35. 7^11 7^35

=7^6 ⋅ 7^5. 7^22. 7^70. 7^11 7^35

As bases are same so powers will be added

=7^6+5+22+ 70+11+35

=7^149

=8.310133e+125

i hope it will help you!

User Amr Mostafa
by
6.3k points